From big data to better patient outcomes - Hulsen, Tim; Friedecký, David; Renz, Harald; Melis, Els; Vermeersch, Pieter; Fernandez-Calle, Pilar (Clinical chemistry and laboratory medicine, 2023)
Among medical specialties, laboratory medicine is the largest producer of structured data and must play a crucial role for the efficient and safe implementation of big data and artificial intelligence in healthcare. The area of personalized therapies and precision medicine has now arrived, with huge data sets not only used for experimental and research approaches, but also in the "real world". Analysis of real world data requires development of legal, procedural and technical infrastructure. The integration of all clinical data sets for any given patient is important and necessary in order to develop a patient-centered treatment approach. Data-driven research comes with its own challenges and solutions. The Findability, Accessibility, Interoperability, and Reusability (FAIR) Guiding Principles provide guidelines to make data findable, accessible, interoperable and reusable to the research community. Federated learning, standards and ontologies are useful to improve robustness of artificial intelligence algorithms working on big data and to increase trust in these algorithms. When dealing with big data, the univariate statistical approach changes to multivariate statistical methods significantly shifting the potential of big data. Combining multiple omics gives previously unsuspected information and provides understanding of scientific questions, an approach which is also called the systems biology approach. Big data and artificial intelligence also offer opportunities for laboratories and the In Vitro Diagnostic industry to optimize the productivity of the laboratory, the quality of laboratory results and ultimately patient outcomes, through tools such as predictive maintenance and "moving average" based on the aggregate of patient results.
Keywords: personalized healthcare; data science; individualizovaná medicína; Artificial Intelligence; Delivery of Health Care; algoritmy; poskytování zdravotní péče; Humans; Precision Medicine; Algorithms; big data; artificial intelligence; precision medicine; patient outcomes; lidé; umělá inteligence; Big Data